Exceptionally Unusual Case of a Self-Inflicted Suicidal Cut Throat Injury - Mezhuneituo Raleng; Anant Prakash Pore; Temsula Alinger (Journal of Trauma and Injury)
Here we present a 43-year-old man who was brought with a self-inflicted cut throat injury; 18 hours after the suicidal attempt. On examination a deep 12 cm cut at the level of the hyoid bone exposing the posterior pharyngeal wall was seen. Emergency surgery with primary repair, tracheostomy and feeding gastrostomy was done. Post-operative period was uneventful and patient recovered without any speech or swallowing abnormalities. Through this article we would like to stress that even in cases of frightening ghastly wounds, by maintaining simple surgical principles we can achieve good outcomes.